2022
DOI: 10.3390/plants11223158
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Physiological Roles of Flavonoids in Plant Environmental Stress Responses and Tolerance

Abstract: Flavonoids are characterized as the low molecular weight polyphenolic compounds universally distributed in planta. They are a chemically varied group of secondary metabolites with a broad range of biological activity. The increasing amount of evidence has demonstrated the various physiological functions of flavonoids in stress response. In this paper, we provide a brief introduction to flavonoids’ biochemistry and biosynthesis. Then, we review the recent findings on the alternation of flavonoid content under d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(63 citation statements)
references
References 184 publications
0
62
1
Order By: Relevance
“…A flavonoids-mediated suppression of ROS generation occurs through four mechanisms, including (i) inhibiting singlet oxygen, (ii) recycling of other antioxidants, (iii) chelating transition metals, and (iv) inhibiting ROS-producing enzymes (cyclooxygenase, lipoxygenase, monooxygenase, and xanthine oxidase). 43,75,76 However, in our study, we observed a decrease in the phenol and flavonoid content after both SA and TP applications compared to their untreated peers, which indicated that neither SA nor TP had a positive impact on phenol and flavonoids.…”
Section: Exogenous Application Of Sa and Tp Improved Physio-biochemic...contrasting
confidence: 78%
See 1 more Smart Citation
“…A flavonoids-mediated suppression of ROS generation occurs through four mechanisms, including (i) inhibiting singlet oxygen, (ii) recycling of other antioxidants, (iii) chelating transition metals, and (iv) inhibiting ROS-producing enzymes (cyclooxygenase, lipoxygenase, monooxygenase, and xanthine oxidase). 43,75,76 However, in our study, we observed a decrease in the phenol and flavonoid content after both SA and TP applications compared to their untreated peers, which indicated that neither SA nor TP had a positive impact on phenol and flavonoids.…”
Section: Exogenous Application Of Sa and Tp Improved Physio-biochemic...contrasting
confidence: 78%
“…The determination of superoxide dismutase (SOD) activity at 560 nm was performed using a spectrophotometer . Moreover, the Shomali et al method was used to determine the activity of peroxidase (POD) and glutathione reductase (GR) at 420 and 340 nm, respectively. Ascorbate peroxidase (APOX) enzyme quantification was performed using a standard technique …”
Section: Methodsmentioning
confidence: 99%
“…It has many biological functions, including defense against biological and abiotic stresses. As important secondary metabolites in plants, flavonoids play an important role in pollen fertility ( Wang, L et al, 2020 ), polar auxin transport ( Zhang et al., 2021 ), and plant resistance to stress injury ( Shomali et al., 2022 ). Previous reports have shown that the accumulation of flavonoids can remove stress-reactive elements from cells, such as free radicals, monopolistic oxygen molecules and peroxides ( Wang et al., 2016 )and reduce their levels after ROS formation, thus exerting antioxidant functions and enhancing plant tolerance to abiotic and biological stresses ( Agati et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…This inference is consistent with the flavonol accumulation (Figure 4) proportional to the decreased L s values. It has previously been demonstrated that phenolic compounds can regulate photosynthesis and the biosynthesis of pigment molecules (Shomali et al, 2022). Stress tolerance in chlorophyll fluorescence variables may have been achieved by Q and K promoting chlorophyll biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, combined Q applications with salt stress increased the net photosynthesis rate. It has been reported that flavonoid accumulation in cells controls metal chelation processes and provides plants tolerance to heavy metal ions(Mira et al, 2002;Shomali et al, 2022). In particular, phenolicmediated improvements in PSI and PSII parameters may be the results of preserving photochemical processes by promoting metal chelation and reducing oxidative damage by K and Q in the chloroplast Parvin et al (2019).…”
mentioning
confidence: 99%